Impact of COVID-19 on Initial Management and Evaluation of Prostate Cancer. Issue 6 (23rd November 2021) - Bernstein, Adrien N.; Talwar, Ruchika; Handorf, Elizabeth; Syed, Kaynaat; Danella, John; Ginzburg, Serge; Belkoff, Laurence; Reese, Adam C.; Tomaszewski, Jeffery; Trabulsi, Edouard; Jacobs, Bruce; Singer, Eric A.; et al.
Abstract: Introduction: The COVID-19 pandemic starkly affected all aspects of health care, forcing many to divert resources towards emergent patient needs while decreasing emphasis on routine cancer care. We compared prostate cancer care before and during the pandemic in a multi-institutional cohort. Methods: A prospective regional collaborative was queried to assess practice pattern variations relative to the initial COVID-19 lockdown (March 16 to May 15, 2020). The preceding 10 months were selected for comparison. The impact of the lockdown was evaluated on the basis of 1) weekly trends in biopsy and radical prostatectomy volumes, 2) comparisons between those undergoing prostate biopsy, and 3) clinicopathological characteristics within radical prostatectomy patients. Categorical variables were compared using Fisher's exact and Pearson's chi-square tests, and Wilcoxon rank sum test to evaluate continuous covariates. Results: Overall, there was a 55% and 39% decline in biopsy and prostatectomy volumes, respectively. During the pandemic, biopsy patients were younger with fewer COVID-19 severity risk factors (17.0% vs 9.7% no risk factors, p=0.023) and prostatectomy patients had higher grade group (GG; 45.6% > GG 4 vs 28%, p=0.01). Large variation in the change in procedural volume was noted across practice sites. Conclusion: In a multi-institutional assessment of surgical and diagnostic delay for prostate cancer, we found a non-uniform decline in procedural volume across sites. Future analyses within this cohort are needed to further discern the effects of care delays related to COVID-19.